2020
DOI: 10.3389/fphys.2020.00719
|View full text |Cite
|
Sign up to set email alerts
|

The Relative Handgrip Strength and Risk of Cardiometabolic Disorders: A Prospective Study

Abstract: Background: This study aims to investigate the association between handgrip strength (HGS) and cardiometabolic disorders (CMD), including hypertension, diabetes, and dyslipidemia, in a prospective study. Methods: The association between HGS and CMD was examined using the data from 5,271 Chinese adult participants ≥45 years old enrolled in the CHARLS (Chinese Health and Retirement Prospective Cohort Study) during 2011-2015. Relative HGS, calculated as maximal absolute HGS from both hands divided by body mass in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 51 publications
1
16
0
Order By: Relevance
“…Ho et al pointed out that the relationship between HGS and health outcomes would not be altered by changing how it is expressed, but the endpoint events in this study did not include new-onset diabetes [23]. Moreover, several studies have also shown that higher relative HGS rather than dominant or absolute HGS was associated with lower cardiometabolic risk [14,15,32]. Remarkably, our research introduced the Harrell's C index, NRI, and IDI to compare the abilities of two HGS expressions in predicting diabetes.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Ho et al pointed out that the relationship between HGS and health outcomes would not be altered by changing how it is expressed, but the endpoint events in this study did not include new-onset diabetes [23]. Moreover, several studies have also shown that higher relative HGS rather than dominant or absolute HGS was associated with lower cardiometabolic risk [14,15,32]. Remarkably, our research introduced the Harrell's C index, NRI, and IDI to compare the abilities of two HGS expressions in predicting diabetes.…”
Section: Discussionmentioning
confidence: 85%
“…In addition, varied HGS measurement methods, including dominant HGS and relative HGS, were applied to explore their associations with diabetes. There are studies pointed out that relative HGS might have an advantage in predicting the risk of cardiovascular biomarkers, metabolic profile, and other cardiometabolic disorders [14][15][16]. Moreover, a Basque study emphasized the need for more in-depth research to help determine whether relative or absolute indicators have more practical applications [17].…”
Section: Introductionmentioning
confidence: 99%
“…Operational personnel did possess more favourable grip strength, lung function, cardiorespiratory fitness levels, engaged in higher amounts of physical activity, and also sat less throughout the day than non-operational personnel. These may be protective factors that could explain the lower odds of hypertension in operational personnel [ 30 , 31 , 32 , 33 , 34 ]. However, it should be noted that the prevalence rates of hypertension for non-operational and operational personnel were not different according to the chi-square analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Previous evidence has consistently documented that police officers have an increased cardiometabolic risk than the general population [ 7 ]. This increased physiological risk existed despite operational personnel having significantly better handgrip strength, lung function, higher physical activity levels, and lower daily sitting, which have been favourably associated with cardiometabolic health [ 30 , 31 , 32 , 33 , 34 ]. This supports the need for occupational health interventions to reduce the risk of cardiometabolic disease in the police, especially those in operational jobs.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that muscle strength is a prognostic factor for all cause death, cardiovascular death, and cardiovascular disease 6,8,9 . Moreover, surveys have also demonstrated the relationship between muscle strength and cardiometabolic risk factors in the elderly 10,11 .…”
Section: Introductionmentioning
confidence: 99%